Major femoral vascular access complications after coronary diagnostic and interventional procedures: A Danish register study. (1st January 2016) - Dencker, Ditte; Pedersen, Frants; Engstrøm, Thomas; Køber, Lars; Højberg, Søren; Nielsen, Michael B.; Schroeder, Torben V.; Lönn, Lars
Abstract: Background: Vascular access complications after coronary angiography (CAG) and percutaneous coronary intervention (PCI) are known to increase morbidity, prolong hospitalization and raise hospital costs. Therefore, risk factor identification and improvement of safety strategies for vascular management are important. We aimed to assess the incidence of major vascular complications related to femoral access, and to identify potential risk factors. Methods: Over a period of six years, 23, 870 index procedures (CAG) were performed in two centres, prospectively entered in the database and retrospectively analysed. Data was obtained from the Eastern Danish Heart Registry and cross-matched with data from the Danish Vascular Registry. Index procedures were defined as the first trans-femoral procedure. Demographic, procedural and mortality data, as well as information on access complications requiring surgery within 30 days were collected. Mortality data were collected for minimum 12 months. Results: We identified 130 (0.54%) access complications requiring surgery; 65 pseudoaneurysms (0.28%), 46 arterial occlusions (0.19%), 15 hematomas (nine groin and six retroperitoneal hematomas) (0.06%), and 4 arterial dissections (0.02%). Risk factors for complications were left sided femoral access (OR 4.11 [2.29–7.37] p < 0.001), peripheral arterial disease (PAD) (OR 2.42 [1.48–3.94] p < 0.0001) and female sex (OR 2.22 [1.51–3.24] p < 0.0001). Conclusion: Vascular complications related to femoral access in coronary diagnostic and interventional procedures are low (0.54%). Risk factors were left sided access, PAD, and female sex.